Diffusive tail anchorage determines velocity and force produced by kinesin-14 between crosslinked microtubules - Annemarie Lüdecke (Nature Portfolio, 2018)
Kinesin-14s, such as Ncd, interact with microtubules with their non-processive motor domains and their diffusive tail domains, but the influence of the tail domains on motor performance is not known. Here the authors show that tail domain slippage limits the velocities and forces generated by Ncd, suggesting it acts as a slippery crosslinker.